relationship to academic endurance among students of psychological counseling and educational guidance departments (Journal of the College of Basic Education, 2022)
The current research aims to identify academic endurance among students of psychological counseling and educational guidance departments, and Does this differ according to their gender, and the researchers the following results:_The research sample represented by the Students of the psychological counseling and educational guidance departments have a high level of academic endurance, which is represented in the student's ability to achieve success in the university despite all the stressful psychological and academic conditions, And also the presence of statistically significant between the sexes and in favor of the fact that females are more committed and follow-up and more inclined to exert effort, and the research came out with a set of recommendations and suggestions